Original paperGenetic polymorphisms of CYP2D6 oxidation in patients with autoimmune bullous diseases - Rychlik-Sych, Mariola; Baranska, Małgorzata; Waszczykowska, Elzbieta; Torzecka, Jolanta Dorota; Zebrowska, Agnieszka; Skretkowicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: Bullous skin diseases, which include, among others pemphigoid, pemphigus, and dermatitis herpetiformis are classified as severe autoimmune dermatoses. It has been shown that a pattern of xenobiotic metabolism may play a role in the pathogenesis of autoimmune diseases. Aim: To estimate whether the CYP2D6 genotype may be considered a predisposing factor in autoimmune bullous diseases induction. Material and methods : The study included 72 patients with autoimmune bullous diseases: 37 with pemphigoid, 21 with pemphigus, and 14 with dermatitis herpetiformis (DH). The CYP2D6 genotypes were analyzed by the polymerase chain reaction fragment length polymorphism (PCR-RFLP) method. Results: Relative risk of DH development for particular genotype carriers expressed by odds ratio (OR) was statistically significantly higher for subjects with CYP2D6*1/CYP2D6*4 (OR = 4.2; p = 0.0104) and 2-fold higher for subjects with CYP2D6*4 (OR = 2.3; p = 0.0351). Conclusions : The results of the present study show that the CYP2D6 oxidation polymorphism cannot be considered a risk factor for development of pemphigoid and pemphigus, however it might have an impact on dermatitis herpetiformis.